Swift Observations of MAXI J1659-152: A Compact Binary with a Black Hole Accretor - Kennea, J.; Romano, P.; Mangano, V.; Beardmore, A.; Evans, P.; Curran, Peter; Krimm, H.; Markwardt, C.; Yamaoka, K. (Institute of Physics Publishing, 2011)
We report on the detection and follow-up high-cadence monitoring observations of MAXI J1659-152, a brightGalactic X-ray binary transient with a likely black hole accretor, by Swift over a 27 day period after its initialoutburst detection. MAXI J1659-152 was discovered almost simultaneously by Swift and the Monitor of All-skyX-ray Image on 2010 September 25, and was monitored intensively from the early stages of the outburst throughthe rise to a brightness of ~0.5 Crab by the Swift X-ray, UV/Optical, and the hard X-ray Burst Alert Telescopes.We present temporal and spectral analysis of the Swift observations. The broadband light curves show variabilitycharacteristic of black hole candidate transients. We present the evolution of thermal and non-thermal componentsof the 0.5–150 keV combined X-ray spectra during the outburst.MAXI J1659-152 displays accretion state changestypically associated with black hole binaries, transitioning from its initial detection in the hard state, to the steeppower-law state, followed by a slow evolution toward the thermal state, signified by an increasingly dominantthermal component associated with the accretion disk, although this state change did not complete before Swiftobservations ended. We observe an anti-correlation between the increasing temperature and decreasing radius ofthe inner edge of the accretion disk, suggesting that the inner edge of the accretion disk infalls toward the blackhole as the disk temperature increases.We observed significant evolution in the absorption column during the initialrise of the outburst, with the absorption almost doubling, suggestive of the presence of an evolving wind from theaccretion disk. We detect quasi-periodic oscillations that evolve with the outburst, as well as irregular shaped dipsthat recur with a period of 2.42±0.09 hr, strongly suggesting an orbital period that would makeMAXI J1659-152the shortest period black hole binary yet known.